2002
DOI: 10.1093/chemse/27.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Odorants Stimulate Microvillar Sensory Neurons

Abstract: The olfactory epithelium (OE) of zebrafish is populated with ciliated and microvillar olfactory sensory neurons (OSNs). Whether distinct classes of odorants specifically activate either of these unique populations of OSNs is unknown. Previously we demonstrated that zebrafish OSNs could be labeled in an activity-dependent fashion by amino acid but not bile acid odorants. To determine which sensory neuron type was stimulated by amino acid odorants, we labeled OSNs using the ion channel permeant probe agmatine (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 30 publications
2
38
0
1
Order By: Relevance
“…Previous works in Carassius carassius showed that this synaptic region, connected with the lateral olfactory tract, mediates feeding behavior (Hamdani et al, 2001b). Retrograde axonal transport studies (Hamdani et al, 2001a;Valentinčič et al, 2005) discovered that the lateral glomerular layer is innervated by microvillous olfactory neurons, known to be stimulated by amino acids (Lipschitz and Michel, 2002). We could hypothesize that in Poecilia reticulata calretinin prevalently identifies the subtypes of crypt and microvillous cells in the mucosa.…”
Section: Discussionmentioning
confidence: 88%
“…Previous works in Carassius carassius showed that this synaptic region, connected with the lateral olfactory tract, mediates feeding behavior (Hamdani et al, 2001b). Retrograde axonal transport studies (Hamdani et al, 2001a;Valentinčič et al, 2005) discovered that the lateral glomerular layer is innervated by microvillous olfactory neurons, known to be stimulated by amino acids (Lipschitz and Michel, 2002). We could hypothesize that in Poecilia reticulata calretinin prevalently identifies the subtypes of crypt and microvillous cells in the mucosa.…”
Section: Discussionmentioning
confidence: 88%
“…One of the goldfish V2R-type receptors and its zebrafish ortholog are activated by amino acids with preferences for arginine and glutamate, respectively (Speca et al, 1999;Kuang et al, 2003;Luu et al, 2004). Activity-dependent labeling of OSNs using a cation channel-permeant probe, agmatine, has shown that amino acid odorants stimulate at least microvillous OSNs in zebrafish (Lipschitz and Michel, 2002). Functional imaging of OB glomeruli in zebrafish using calcium-and voltage-sensitive dyes has revealed that various amino acids and nucleotides elicit activation of glomeruli in the lateral region of the OB Korsching, 1997, 1998).…”
Section: Odorant Response Specificities Of Ciliated and Microvillous mentioning
confidence: 99%
“…In fishes there are three types of sensory neuron; the ciliated and microvillous sensory neurons, and crypt cells. The sensory neurons express different types of odorant receptors and respond to different classes of stimuli (Hansen et al, 2003;Lipschitz and Michel, 2002;Sato and Suzuki, 2001). These classes of sensory neurons send their axons to distinct and segregated regions in the olfactory bulb (Hansen et al, 2003;Koide et al, 2009;Sato et al, 2005).…”
Section: Introductionmentioning
confidence: 99%